The influence of breastfeeding technique education on knowledge of lactation problem prevention - Siregar, Rohani (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Proper breastfeeding techniques are essential for maintaining optimal breast milk production. Incorrect application of these techniques may result in nipple trauma and discourage mothers from breastfeeding. Inadequate breastfeeding can lead to infant malnutrition, increased susceptibility to illness, and, in severe cases, mortality. Health education serves as an effective strategy for postpartum mothers, as it provides knowledge that fosters behavioral change and reduces the risk of exclusive breastfeeding failure.Objectives: This study aimed to evaluate the effect of breastfeeding technique education on improving postpartum mothers’ knowledge in preventing lactation problems.Methods: A quantitative study with a pre-experimental design, specifically a one-group pretestâ€“posttest approach, was conducted. The sample comprised 26 respondents selected through total sampling. Data were analyzed using univariate methods to describe knowledge levels before and after the intervention, and bivariate methods to assess differences between the two measurement points. The Wilcoxon test was applied because the data were not normally distributed (p < 0.05). Results: The findings revealed a significant effect of breastfeeding technique education on the improvement of postpartum mothers’ knowledge in preventing lactation problems, with a p-value of 0.000 (< Î± = 0.05). Conclusions: Providing education and information on breastfeeding techniques, supported by healthcare professionals, particularly midwives, is crucial. This intervention has been demonstrated to be an effective strategy for enhancing breastfeeding success and preventing lactation-related problems